PEMBANGUNAN MARKET PLACE UNTUK UMKM PADA DESA LUMBAN PEA TIMUR - Harlen G. Simanullang; Marlyna Infryanty Hutapea; Indra Kelana Jaya; Jeudi A. T. P. Sianturi; Yolanda Y. P. Rumapea; Margaretha Yohanna (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
Community Service (PkM) was carried out by the Indonesian Methodist University by providing an application in the form of a marketplace for MSMEs in Lumban Pea Timur Village. This marketplace is designed to suit the needs of the community and MSME actors in the village. This PkM was held on June 9, 2022 in collaboration with the Department of Industry, Trade and Cooperatives (PERINDAGKOP) of Toba Regency and invited several representatives of SMEs in Lumban Pea Timur Village. The method used is to explain the use of the marketplace and how to use it. Furthermore, MSME actors are given the opportunity to ask questions about the use of the marketplace. The results of the PkM with the application of the marketplace in East Lumban Pea Village are very effective in helping to increase marketing, sales of regional products and the regional economy of Toba Regency, especially East Lumban Pea Village. In addition, the community also gets a positive impact, namely increasing knowledge about digital media independently to market and sell products produced by MSMEs.